2017
DOI: 10.1177/1541931213601656
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Events and Over-the-Counter (OTC) Drugs: Is Inappropriate Labeling the Problem? - The Case of Acetaminophen

Abstract: Incorrect use of acetaminophen that results in severe liver injury is among the most common adverse drug events (ADEs) in the United States of America (USA), and other countries around the world. Compared to any other drug, it is also on the top for emergency calls, emergency room visits, and acute liver failure in the USA. Consequently, regulating acetaminophen has become a heated and unresolved public debate. During the last decades, multiple efforts have taken place to address the issue, mostly focused on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…These individuals are not necessarily characterized by a disease condition, although studies often examine groups bounded by age or other demographics (e.g., children, Latinos), geography (e.g., rural, residing in low and middle income countries), or disease risk factors (e.g., obesity, sedentary lifestyle). There have been a number of patient ergonomics studies on health promotion, such as people's use of anecdotal health information on the Internet (Madathil et al, 2014); understanding safety information on over-thecounter medication labels (Rojas & Li, 2017); and factors affecting sleep in adolescents (Vredenburgh, 2017). By far the largest segment of patient ergonomics studies in health promotion addresses technologies for health promotion.…”
Section: Beyond Disease: Health Promotionmentioning
confidence: 99%
“…These individuals are not necessarily characterized by a disease condition, although studies often examine groups bounded by age or other demographics (e.g., children, Latinos), geography (e.g., rural, residing in low and middle income countries), or disease risk factors (e.g., obesity, sedentary lifestyle). There have been a number of patient ergonomics studies on health promotion, such as people's use of anecdotal health information on the Internet (Madathil et al, 2014); understanding safety information on over-thecounter medication labels (Rojas & Li, 2017); and factors affecting sleep in adolescents (Vredenburgh, 2017). By far the largest segment of patient ergonomics studies in health promotion addresses technologies for health promotion.…”
Section: Beyond Disease: Health Promotionmentioning
confidence: 99%
“…Data have shown that the proportion of acute liver failure (ALF) cases resulting from deliberate or accidental overdoses of paracetamol, mainly in opioid/paracetamol combination products, increased from 28% in 1998 to 51% in 2003. Thus, the elimination of prescription paracetamol combination products was recommend by the FDA advisory committee in June 2009 [6, 10].…”
Section: Introductionmentioning
confidence: 99%